Determinants of Corporate Dividend Policy: An Empirical Analysis of UK Listed Companies - PENG, SHIQIN (2012)
This paper investigates the common determinants of dividend payout policy of UK listed companies on London Stock Exchange FTSE 350 over a ten-year period from2002 to 2011. The focus of this research will be put on dividend policy. Six research hypotheses are proposed, which derived from main dividend policy theories to examine the influencing factors. This paper chooses six factors for the regression test. A panel dataset has been created and the fixed effects model is regarded as the Best-fit model. The variables chosen as factors affecting the decisions of dividend are firm size, profitability, investment opportunity, financial leverage, tax and retained earnings for lifecycle. Firm size, profitability and life cycle positively influence the dividend per share, while the tax shows a negative effect on dividends. These results are significantly in the predicted direction and consistent with various empirical studies. However, the regression results of investment opportunity and financial leverage are insignificant; they do not explain the dividend in advance. Consequently, this study may provide some understanding in the determinants of dividend policy for UK listed firms.